Enhancing Biogas Production Via Single and Mixing Anaerobic Digestion of Food Waste and Coconut Waste - Selaman, Rafidah; Haslynda, D N; Achoi, M F; A Jawan, A; Lepit, A (Balai Publikasi Indonesia, 2025)
Food waste (FW) and coconut waste (CW) contribute significantly to environmental pollution, highlighting the need for sustainable waste management solutions. This study investigates the anaerobic digestion (AD) of FW and dried CW, comparing the efficiency of single and mixing digestion approaches in biogas production. The research examines the physical properties of both substrates and evaluates their biogas production potential using anaerobic single and mixing digestion techniques. Standard methods were employed to analyse total solids (TS), volatile solids (VS), and pH. The experiments were conducted in Duran bottles at mesophilic temperatures (26°C–32°C) with a se t inoculum-to-sample ratio. Biogas production was measured using the water displacement method over 10 days. The TS values for FW and CW were 46.00% (±0.05) and 60.00% (±0.04), respectively, while their VS values were 97.73% (±0.05) and 93.75% (±0.07), respectively. The pH analysis indicated that both substrates were in an acidic state; the value was near the optimum value of AD. Biogas recovery results indicates that mixing digestion of FW and CW produced the highest yield, reaching 786.00 mL (±0.02) on day 8. In contrast, single digestion of FW and CW yielded 425.0 mL (±0.04) (day 8) and 475.0 mL (±0.05) (day 7), respectively. These findings demonstrate that mixing digestion significantly enhances biogas production due to improved nutrient balance and microbial activity. Additionally, mixing digestion stabilizes the AD process, leading to greater efficiency and energy recovery. This study highlights the potential of FW and CW as viable feedstocks for biogas generation, offering a sustainable waste management alternative. By optimizing AD systems, this research contributes to renewable energy development and supports sustainable waste utilization practices